2012
DOI: 10.1002/lt.23440
|View full text |Cite
|
Sign up to set email alerts
|

Recipient survival and graft survival are not diminished by simultaneous liver-kidney transplantation: An analysis of the united network for organ sharing database

Abstract: Recipients of solitary liver and kidney transplants are living longer, and this increases their risk of long‐term complications such as recurrent hepatitis C virus (HCV) and drug‐induced nephrotoxicity. These complications may require retransplantation. Since the adoption of the Model for End‐Stage Liver Disease, the number of simultaneous liver‐kidney transplantation (SLK) procedures has increased. However, there are no standardized criteria for organ allocation to SLK candidates. The aims of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 57 publications
3
61
0
1
Order By: Relevance
“…100 Data from the United Network for Organ Sharing registry have demonstrated that patient survival in com bined liver-kidney transplantation in patients with HCV infection is higher than that observed in patients who underwent renal transplantation followed by liver trans plantation, or vice versa. 101 An additional study using data from this registry showed that in recipients of renal trans plants with both HCV and HIV, the HCV infection was the first determinant of patient survival, thus suggesting that treatment of HCV infection should be mandatory. 102 Graft survival Several studies, predominantly retrospective in design, have demonstrated that patients with HCV infection experience lower graft survival than do patients who do not have HCV infection.…”
Section: Effect Of Hcv Infection On Survivalmentioning
confidence: 98%
See 1 more Smart Citation
“…100 Data from the United Network for Organ Sharing registry have demonstrated that patient survival in com bined liver-kidney transplantation in patients with HCV infection is higher than that observed in patients who underwent renal transplantation followed by liver trans plantation, or vice versa. 101 An additional study using data from this registry showed that in recipients of renal trans plants with both HCV and HIV, the HCV infection was the first determinant of patient survival, thus suggesting that treatment of HCV infection should be mandatory. 102 Graft survival Several studies, predominantly retrospective in design, have demonstrated that patients with HCV infection experience lower graft survival than do patients who do not have HCV infection.…”
Section: Effect Of Hcv Infection On Survivalmentioning
confidence: 98%
“…14,103 The rate of graft survival in combined liver-kidney transplantation is improved over separate transplanta tion procedures. 101 Patients infected with both HCV and HIV show lower graft survival as compared with renal transplant recipients infected with HIV alone. 100…”
Section: Effect Of Hcv Infection On Survivalmentioning
confidence: 98%
“…The survival for CLKT, however, is superior to kidney transplant (KT) after LT or LT after KT. 8,9 The complexity of CLKT derives not only from the surgical procedure itself, but also from postoperative management. Recipients of LT are frequently coagulopathic and often require pressors to correct perioperative hypotension.…”
mentioning
confidence: 99%
“…We chose the study period based on availability of a full complement of donor characteristics, up to the implementation of the Kidney Allocation System (KAS). We defined SLK transplantation as deceased donor liver and kidney transplantations occurring within 2 days in the same recipient 15,16 . We aimed to establish a cohort of adult SLK recipients without prolonged pretransplant dialysis, ie, not on dialysis, or on dialysis for fewer than 90 days at the time of transplantation, since the SLK controversy is mostly concentrated in this patient population.…”
Section: Methodsmentioning
confidence: 99%